A functor that reflects and preserves compactness and connectedness (2005)
We present an equivalence between the compactness of atopological space and the compactness of a quotient space obtained through a natural equivalence relation. By means of this equivalence, the study of compactness in general is reduced to that of T0 topological spaces.